Influence of Rumen Protected Fat Supplementation on Nutrient Intake and Feed Conversion Efficiency in Buffaloes - Prajapati, Dhruv C.; Patel, Dilip C.; Parmar, Abhishek B.; Patel, Shaweta N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was carried out to assess the effects of supplementation of bypass fat for one month prepartum and three months postpartum on nutrient intake and feed conversion efficiency for milk production in buffaloes. Advanced pregnant buffaloes (n=32, 2-3 parity) were selected at farmers’ doorstep, and were divided into two equal groups, each of 16 animals, on the basis of previous lactation milk production and fat %. Animals in T1 group (n=16, control) received farmers’ feeding schedule, and those in T2 group were additionally supplemented with bypass fat @ 100 g/head/d during prepartum and 20 g/kg of milk yield during early lactation. Average daily DM and DCP intake did not differ significantly in control and treatment group, whereas average daily TDN intake was found significantly higher in treatment group during postpartum phase. Whole milk yield (kg/head/d) of buffaloes in T2 group was significantly (P<0.05) higher than T1 (5.43±0.07 vs. 4.50+0.04). Feed conversion efficiency (kg intake/kg whole milk) of DM (2.40±0.04 vs. 1.99±0.02), DCP (133.50±1.84 vs. 111.56±01.20) and TDN (1.53±0.02 vs. 1.31±0.01) was superior (P<0.05) in bypass fat group, and similar was the trend for 6% FCM yield. Daily feed cost (Rs. 101.66±0.45 vs. 92.98±0.64) and average realizable receipt from sale of milk (Rs. 231.12±1.46 vs. 165.88±1.39/head) were higher (p<0.05) in T2 group over control. The findings indicated that the bypass fat supplement @ 100 g/head/day one month before parturition and 20 g/kg milk yield during early lactation to buffaloes was economically advantageous in terms of increased milk yield and better feed conversion efficiency.